Effect of salt solution treatment on impurity removal: A case study on phosphogypsum. Issue 3 (5th November 2022) - Avşar, Cemre; Ertunç, Suna
Abstract: This study gives a brief demonstration of impurity removal efficiency upon salt solution treatment of phosphogypsum (PG). The experimental set up has been designed according to a multi‐variable Box–Behnken Design (BBD) with stirring time, solid: liquid (PG:salt solution) ratio and temperature as the conducted in various salt solutions. PG sample has been treated with sea water, 5% NaCl and 10% NaCl solutions according to the BBD matrix. Fluoride (F), copper (Cu), manganese (Mn), and nickel (Ni) amounts in the PG sample have been measured upon pre‐ and post‐treatment with salt solutions. Among other operating conditions, temperature has been the dominant factor on fluoride removal efficiency, and responses for the factors determined in the experiment runs indicated that a significant correlation could be established between temperature and fluoride removal, sea water being the most efficient salt solution. Higher copper, manganese, and nickel removal efficiencies have been observed in single salt NaCl solution systems however no significant correlation could be established between factors. Results indicate that pre‐treatment of PG located near coastal regions with sea water can be a cost‐effective approach and applicable on industrial scale when fluoride removal is of importance.